DISTORTED-WAVE CALCULATIONS OF VIBRATIONAL-EXCITATION IN CO2+HE AND CO2+AR COLLISIONS - Novak, M; Balintkurti, G; Clary, D (1987)
Cross sections for the vibrational excitation and relaxation of CO2 through collisions with He and Ar atoms have been computed using several approximate methods. They all employ the infinite-order sudden approximation for the rotational motion. The vibrational motion is treated using both exact close-coupling and distorted wave techniques. The latter approximate method permits the extension of the calculation to much higher collision energies. The validity of the distorted wave approximation is examined and is shown to be particularly good for the dominant inelastic processes in He+CO2, leading to errors of the order of 7%. These become progressively greater for smaller cross sections. The excitation cross sections are reported for several vibrational transitions over an extended energy range up to 1.36 eV. © 1987.